Express check-in: developing a personal health record for patients admitted to hospital with medical emergencies: a mixed-method feasibility study. (19th August 2021) - Subbe, Christian P; Tomos, Hawys; Jones, Gwenlli Mai; Barach, Paul
Abstract: Background: Patient participation is increasingly recognized as a key component in the redesign of healthcare processes and is advocated as a means to improve patient safety. Objective: To explore the usage of participatory engagement in patient-created and co-designed medical records for emergency admission to the hospital. Methods: design: prospective iterative development and feasibility testing of personal health records; setting: an acute medical unit in a university-affiliated hospital; participants: patients admitted to hospital for medical emergencies; interventions: we used a design-led development of personal health record prototypes and feasibility testing of records completed by patients during the process of emergency admission. 'Express-check-in' records contained items of social history, screening questions for sepsis and acute kidney injury in addition to the patients' ideas, concerns and expectations; main outcome measures: the outcome metrics focused on feasibility and a selection of quality domains, namely effectiveness of recording relevant history, time efficiency of the documentation process, patient-centredness of resulting records and staff and patient feedback. The incidence of sepsis and acute kidney injury were used as surrogate measures for assessing the safety impact. Results: The medical record prototypes were developed in an iterative fashion and tested with 100 patients, in which 39 patients were 70 or older and 25 patients were classified as clinically frail. Ninety-six per cent of the data items were completed by patients with no or minimal help from healthcare professionals. The completeness of these patient records was superior to that of the corresponding medical records in that they contained deeply held beliefs and fears, whereas concerns and expectations recorded by patients were only mirrored in a small proportion of the formal clinical records. The sepsis self-screening tool identified 68% of patients requiring treatment with antibiotics. The intervention was feasible, independent of the level of formal education and effective in frail and elderly patients with support from family and staff. The prototyped records were well received and felt to be practical by patients and staff. The staff indicated that reading the patients' documentation led to significant changes in their clinical management. Conclusions: Medical record accessibility to patients during hospital care contributes to the co-management of personal healthcare and might add critical information over and above the records compiled by healthcare professionals.